A Teacher educators’ conceptions of teaching and learning in the early years - Ebrahim, Hasina Banu; Martin, C; Koen, MP; Daries, G; Olivier, M; Van Zyl, E (South African Journal of Higher Education, 2016)
The aim of this article is to report on a qualitative study that investigated teacher educator’s conceptions of teaching and learning. The study was undertaken to inform the development of the new Bachelor of Education in the Early Childhood and Foundation Phase (ECFP) at the University of Free State. The data for the study was produced with six teacher educators participating in blogs and group meetings. The findings show that teacher educators’ conceptions of teaching and learning are drawn from a variety of frames of reference and theoretical ideas. Although this is the case, their conceptions all point towards process-oriented and constructivist views of teaching and learning. This study draws attention to actions required for enabling teacher educators to function in more argentic ways.